(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Konok М. Мethodological requirements to realization of intersubject connections at future technologies teacher preparation. In article made an attempt to the problem’s separate aspect of intersubject connections strengthening decision on employments of professional disciplines at future technologies teachers preparation.